2022
DOI: 10.3389/fnbeh.2022.799015
|View full text |Cite
|
Sign up to set email alerts
|

On the Similarity Between the Reinforcing and the Discriminative Properties of Intracranial Self-Stimulation

Abstract: Rats work very hard for intracranial self-stimulation (ICSS) and tradeoff effort or time allocation for intensity and frequency parameters producing a sigmoidal function of the subjective reward magnitude of ICSS. Previous studies using electrical intracranial stimuli (ICS) as a discriminative cue focused on estimating detection thresholds or on the discrimination between intensities. To our knowledge, there is no direct comparison of the reinforcer tradeoff functions with the discriminative functions. Rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…In previous work that examined time allocation we observed deceasing time allocation as work requirement increased (e.g. Trujillo-Pisanty et al 2020; Velazquez-Martinez et al 2022). However, it should be noted that in previous studies available time for responding (usually enough time to collect a fixed number or reinforcers) was controlled by the schedule, but in the PR schedule, both PS R P duration and IS R T was controlled by the subject.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…In previous work that examined time allocation we observed deceasing time allocation as work requirement increased (e.g. Trujillo-Pisanty et al 2020; Velazquez-Martinez et al 2022). However, it should be noted that in previous studies available time for responding (usually enough time to collect a fixed number or reinforcers) was controlled by the schedule, but in the PR schedule, both PS R P duration and IS R T was controlled by the subject.…”
Section: Discussionmentioning
confidence: 73%
“…It has been suggested that a more basic unit of measurement than actual numbers of discrete responses may be time allocated to an activity (Baum and Rachlin 1969); then, the hold-down response that excludes any other behavioral responses may truly reflect WT. Hold-down responses had been used successfully by the Reward Mountain Model to have an exact estimation of time allocation and, as commented previously, demonstrated that time allocation is related to the joint function of reward strength (frequency, amplitude or train duration) and the cumulated time or effort to harvest rewards in various electrical-(Arvanitogiannis and Shizgal 2008; Hernandez et al 2010; Trujillo-Pisanty et al 2011; Hernandez et al 2012; Trujillo-Pisanty, Conover, and Shizgal 2013; Solomon et al 2015; Solomon, Conover, and Shizgal 2017; Trujillo-Pisanty et al 2020; Velazquez-Martinez et al 2022) and optical-ICSS (Pallikaras et al 2022) procedures. Worth to notice is that even the shortest hold requirements rarely were completed with a single lever-holding response, but rather lever was released for very brief periods several times within the IS R T (Rider and Kametani 1984).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations